Position control to expand the headlights’ angle of a car by DC motor drive system using PSO algorithm for speed loop - Thi Hoai Thu Anh, An; Cong Duc, Pham; Dinh Huan, Le (Bulletin of Electrical Engineering and Informatics, 2025)
Today, along with the robust development of society, cars are almost considered a primary means of transportation. This article focuses on designing headlight controls for older car models that are not equipped with adaptive headlight systems (AHS), which are different from modern cars such as Porsche, BMW, Audi, and Mercedes-Benz vehicles. The design is for a lighting system that operates during nighttime to improve illumination and enhance visibility in curves, with cost-effective and suitable solutions for average vehicles to ensure safety. This system uses a DC motor to control the headlight angle based on the steering wheel rotation. It is combined with the particle swarm optimization (PSO) algorithm to find the best response parameters for the proportional-integral-derivative (PID) controller. Research results on the MATLAB/Simulink and the experimental model show that the model established by this method has good accuracy, the controllers can significantly reduce the excessive deviation of the headlights’ operational precision, and traffic accidents can be minimized, increasing safety for users.